Hubungan Tingkat Kecemasan dengan Kejadian Insomnia pada Lansia di BPSTW Unit Budi Luhur Kasongan Bantul Yogyakarta - Riska Dyah Ayu Kusumaningtyas; Arita Murwani (Caring : Jurnal Keperawatan, 2020)
Old age is a cycle of human life experienced and can not be avoided by anyone. The process of becoming elderly, both physically and psychologically, is generally characterized by a deterioration in the quality of life and the functions of the limbs. Mental disorders are closely related to sleep disorder or insomnia is anxiety, insomnia is a disorder of initiating or maintaining sleep.To determine the relationship of anxiety levels with the incidence of insomnia in the elderly at BPSTW Unit Budi Luhur Kasongan Bantul Yogyakarta.There is a relationship between anxiety level and the incidence of insomnia in the elderly BPSTW Unit Budi Luhur Kasongan Bantul Yogyakarta. This research is a quantitative research in the form of correlational with cross sectional approach. The population in this study were all the elderly that were recorded in Budi Luhur Community Dwelling at Kasongan Street No.88, Kajen, Bangunjiwo, Kasihan, Bantul Yogyakarta. The sample in this study was 76 respondents with a sampling technique using purposive sampling hypothesis using the Kendall-Tau. Based on the results of the study showed the level of anxiety in the medium category of 24 respondents (31.6%), and the incidence of insomnia in the elderly in the moderate category of 35 responden (46.1%),from the results of the controltest or the results obtained p-value 0.012 with result p-alpha = 0,05 the value p-value < score p-alpha (0,012 < 0.05) so the level of anxiety has a relationship to the incidence of insomnia in the elderly in Budi Luhur Community Dwelling at Kasongan Bantul Yogyakarta. There is a relationship between anxiety level and the incidence of insomnia in the elderly in Budi Luhur Community Dwelling at Kasongan Bantul Yogyakarta.